Effect of HEC (Hydroxyethyl Cellulose) Polymer on Nanoemulsion-Based Curcumin Transdermal Patch Release - Rahmatia Is. Kaluku; Robert Tungadi; Nur Ain Thomas (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
Curcumin a hydrophobic polyphenolic compound and water-insoluble that creates low systemic bioavailability inside the body, has broad pharmacological activity, including anti-inflammation. This study aims to formulate, characterize and evaluate the nanoemulsion based on curcumin through an in vitro transdermal patch preparation. This study starts from formulating a curcumin nanoemulsion solution and characterizing the particle size of curcumin through PSA (Particle Size Analyzer). Further, it formulates the transdermal patch preparation with the smallest curcumin particles within three concentrations (HEC 0,625%, 1,25%, and 2,5%) combined with HPMC 2,5% as polymer. Those formulations are evaluated through organoleptic, thickness, weight uniformity, humidity, and folding resistance tests. In the next step, this study examines the penetration through an in vitro by using a franz diffusion cell within 72 hours. The result shows increasing penetration on each formula where the best penetrations occur in the 15th and 24th hours. It also discovers that the formula containing HEC 2,5% (2c) creates the highest cumulative drug penetration (15,83%). Therefore, it deduces that curcumin nanoemulsion in the transdermal patch has good characteristics and is compatible between drug and polymer.